The Influence of Intant Massage to Weight Gains in Low Birth Weight Infant (LBW) : A Systematic Review - Atika; Djuari, Lilik; Manaf, Hafizh Al Ghifari; Bachtiar, Daffa Ardhi; Sabrina, Annisa Maya; Ismahendra, Naufal Agus; Soediono, Mochammad Ridhwan; Yuliana, Sitti Khofifah; Razaan, Muhammad Farras; Karim, Yustika Ayoustira (Journal of Community Medicine and Public Health Research, 2024)
Growth and development is a significant phase that cannot be replicated, underscoring the need for meticulous attention, particularly for those born with low birth weight (LBW). LBW can be stimulated using infant massage. This research aimed to evaluate the impact of infant massage on weight gain among LBW infants. This is a systematic review using PICOS framework, investigating studies from 2018 to 2023 in databases including Cochrane, PubMed, ScienceDirect, and Scopus. The inclusion criteria involved full-text access and the keywords low birth weight, weight gain, and massage. The initial search yielded 1913 literature, which were screened based on publication year and type, resulting in 122 articles. After being examined, 119 articles were excluded due to duplication, using non-English language, involving non-LBW, different outcomes, and non-RCT, leaving three articles. The assessment of literature quality was conducted using the JBI Critical Appraisal Checklist for Systematic Reviews and Research Syntheses. The results of outcome measurements and group comparisons across the three studies exhibited congruence. In conclusion, the finding indicated that infants who underwent massage intervention exhibited weight gain, as did those who did not undergo such intervention. Furthermore, infants who received massage intervention experienced a more pronounced increase in weight compared to their counterparts who did not undergo massage intervention.